Islam and Civilization: Classical Arabic Studies before the Prophet and the Birth of Islamic Education during the Time of the Prophet - Alimni, Alimni; Gustina, Zapia; Yakubu, Muhammad Auwal; Alaldaya, Rudyn (Indonesian Journal of Research in Islamic Studies, 2025)
Background: Before the arrival of Islam, Arab society lived in the Jahiliyyah period, which was characterized by polytheism, social instability, and low moral standards. Objective: This study aims to explore and analyze social and educational changes in pre-Prophet Classical Arabia, examining the emergence of the Islamic education system during the time of the Prophet Muhammad, including the transition from informal oral traditions to a more structured, revelation-based education system. Method: The research employs a literature study approach, specifically a Systematic Literature Review (SLR). Primary and secondary sources are analyzed thematically to compare the characteristics of Arab society before and after the prophethood of the Prophet Muhammad SAW, with a focus on social, economic, and educational dimensions. Results: The findings show that the arrival of Islam through the Prophet Muhammad SAW brought radical changes in the socio-economic and educational order. Education, which initially evolved from informal and oral traditions, developed into a structured system centered on revelation, literacy (including reading and writing), and early institutions such as the Kuttab and Suffah, as well as the strengthening of scientific ethics through the values of monotheism, justice, and morality. Conclusion: The shift from the pre-Islamic to the prophetic era transformed education from oral traditions to structured learning, strengthening moral foundations, expanding literacy, and redefining the link between knowledge, religion, and society. Contribution: This research provides a historical and critical perspective on the emergence of Islamic education as a response to the limitations of pre-Islamic society, framing education as a driver of social change and a conceptual basis for developing value-based curricula and modern educational models.